Effects of aminoguanidine on dermal collagen structure and TGF-beta expression in streptozotocin induced diabetic rats - (:unkn) unknown (My University, 2005)
Objective: The aim of this study was to evaluate the effects of aminoguanidine treatment on dermal extracellular matrix protein expression and collagen structure in a diabetic rat model. Methods: Twelve Wistar Albino male rats were induced diabetes by streptozosin. Six rats were given aminoguanidine in drinking water; remaining 6 rats were followed as diabetic controls. Additional six rats were followed as healthy controls. After an 8-week follow-up period skin samples obtained and evaluated for light microscopy and immunohistochemistry for collagen IV and TGF-β. Results: Light microscopy revealed increase in basement membrane thickness, dermal edema, vascular membrane thickness, increase in endothelial proliferation and perivascular degeneration in diabetic rats. Immunohistochemical staining displayed reduction in collagen IV and TGF-β in diabetic group compared to others. All these changes were ameliorated with aminoguanidine treatment. Conclusion: This study confirms microscopic abnormalities in clinically normal skin of diabetics that can be prevented with aminoguanidine treatment.
Keywords: Aminoguanidine; Diabetes Mellitus; Skin